KÑ€Ð¸Ð¾Ð»ÑƒÑ‡ÐµÐ²Ð¾Ð¹ Ð¿Ð°Ñ‚Ð¾Ð¼Ð¾Ñ€Ñ„Ð¾Ð· Ð°Ð´ÐµÐ½Ð¾ÐºÐ°Ñ€Ñ†Ð¸Ð½Ð¾Ð¼Ñ‹ Ð“ÐµÑ€ÐµÐ½Ð° - Mikhanovky, A. A.; Gusakova, V. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2002)
The authors studied a cryoray pathomorphosis of Guerin’s adenocarcinoma depending on the terms of pre-x-ray tumour cryodestruction and total focal dose (TFD) of irradiation. The investigations have shown that X-ray therapy of Guerin’s adenocarcinoma in the combination with a tumour cryodestruction in 24 hrs before the irradiation, shows more manifested inhibiting effect comparing to the tumours, subjected to cryoeffect before 48hrs, and the control group.